Dynamic artificial light-harvesting systems based on rotaxane dendrimers. (June 2020) - Li, Wei-Jian; Wang, Xu-Qing; Wang, Wei; Hu, Zhubin; Ke, Yubin; Jiang, Hanqiu; He, Chunyong; Wang, Xueli; Hu, Yi-Xiong; Jia, Pei-Pei; Yin, Panchao; Chen, Jinquan; et al.
Abstract: Although the preparation of artificial light-harvesting systems (ALHs) has attracted increasing attention, dynamic regulation of antenna effect in ALHs has been still a major challenge. Herein, we constructed a family of new rotaxane dendrimers containing up to fifty-six anthracene moieties (energy donor) on the wheels of the rotaxane units and one zinc(II) porphyrin moiety (energy acceptor) at the central core. Notably, the resultant rotaxane dendrimers incorporate a large number of rotaxane subunits on the dendritic skeleton in a monodisperse manner, which thus allowed for the high energy transfer efficiencies and antenna effects. More importantly, with the addition and removal of acetate anions, the directional and reversible motion of rotaxane unit on each axis was realized, thus leading to dynamic regulation of antenna effect in resultant rotaxane dendrimers. Graphical abstract: Image, graphical abstract